2014
DOI: 10.2136/vzj2014.02.0015
|View full text |Cite
|
Sign up to set email alerts
|

Constraints on the Sources and Production Mechanisms of Dissolved Organic Matter in Soils from Molecular Biomarkers

Abstract: International audienceSpatio-temporal modifications of the composition of dissolved organic matter (DOM) from a wetland in an agricultural catchment were investigated using thermally assisted hydrolysis and methylation with tetramethylammonium hydroxide coupled to gas chromatography and mass spectrometry (THM-GC–MS). The results were compared with previous data acquired on the same samples using ultraviolet spectroscopy and the stable C isotope ratio. The correlation between molecular markers and bulk-scale de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(53 citation statements)
references
References 84 publications
4
49
0
Order By: Relevance
“…Our observations are consistent with previous laboratory experiments that have shown that soil rewetting after a dry period could release organic and inorganic P as a result of microbial biomass being killed by osmotic shock (Blackwell et al, 2010;Turner and Haygarth, 2001). Previous monitoring campaigns in the same watershed, but focusing on the composition of dissolved organic matter using ultraviolet spectrometry, carbon isotopes and molecular biomarkers highlighted the release of microbial-derived organic compounds in the soil solution at the same time of the year (Jeanneau et al, 2014;Lambert et al, 2013). Hence, the most probable mechanism causing P release when the water table rose at the beginning of the hydrological season was mobilization of a P pool of microbial origin, limited in size, which can migrate under water saturated conditions (McGechan et al, 2005).…”
Section: In Both Rw a And B Mrp Concentrations In The Soil Solution supporting
confidence: 91%
See 2 more Smart Citations
“…Our observations are consistent with previous laboratory experiments that have shown that soil rewetting after a dry period could release organic and inorganic P as a result of microbial biomass being killed by osmotic shock (Blackwell et al, 2010;Turner and Haygarth, 2001). Previous monitoring campaigns in the same watershed, but focusing on the composition of dissolved organic matter using ultraviolet spectrometry, carbon isotopes and molecular biomarkers highlighted the release of microbial-derived organic compounds in the soil solution at the same time of the year (Jeanneau et al, 2014;Lambert et al, 2013). Hence, the most probable mechanism causing P release when the water table rose at the beginning of the hydrological season was mobilization of a P pool of microbial origin, limited in size, which can migrate under water saturated conditions (McGechan et al, 2005).…”
Section: In Both Rw a And B Mrp Concentrations In The Soil Solution supporting
confidence: 91%
“…This indicates that reductive dissolution of Fe (hydr)oxides is the mechanism causing the P release observed under anoxic conditions (Carlyle and Hill, 2001). Anoxic conditions at this time of year were due to low rainfall in a period of high water table, which decreased water velocity and thus water oxygenation (Jeanneau et al, 2014). As a result, Fe (hydr)oxides became solubilized as Fe 2þ (Bourri e et al, 1999), which released previously adsorbed P (Hoffmann et al, 2009;Vidon et al, 2010).…”
Section: In Both Rw a And B Mrp Concentrations In The Soil Solution mentioning
confidence: 97%
See 1 more Smart Citation
“…1) well-known hydrologic and biogeochemical context and has already been the subject of numerous investigations of the sources and dynamics of both soil and stream DOM (Morel et al, 2009;Lambert et al, 2011Lambert et al, , 2013Lambert et al, , 2014Aubert et al, 2013;Jeanneau et al, 2014Jeanneau et al, , 2015. Table S1).…”
Section: Sampling and Sample Preparationmentioning
confidence: 99%
“…FAs with a high molecular weight (> C19 : 0) are from plant origin while FAs with a low molecular weight (< C19 : 0) come from microbial origin except for C16 : 0 and C18 : 0 which can be derived from both (Frostegard et al, 1993;Zelles, 1999). The proportion of microbial markers among the analysed compounds (f mic ) was calculated according to Jeanneau et al (2014).…”
Section: Molecular Analysismentioning
confidence: 99%